The public-interest action in South Africa: the transformative injunction of the South African Constitution - Swanepoel, C. F. (Faculty of Law, University of the Free State, 2016)
The insertion of sec. 38 in the Constitution of the Republic of South Africa, 1996, has seen substantial broadening of standing opportunities for litigants since the advent of the country’s constitutional dispensation. Amongst others, it has led to the development of public-interest litigation in terms of sec. 38(d), which is in line with the constitutional mandate of societal transformation. The full impact of the latter constitutional provision has recently been illustrated by the public and legal controversy surrounding the South African government’s failure to arrest Sudanese President Omar Hassan Ahmed Al-Bashir while he was attending an AU summit in Johannesburg. The Southern African Litigation Centre’s application to enforce the International Criminal Court’s warrant of arrest against Al-Bashir was brought in the centre’s own name, but was supplemented by public interest. Currently, however, there is neither case law nor legislation explicitly dealing with a pure public-interest action in South Africa, which leaves litigants and the judiciary without any guiding principles. Therefore, this article draws on the South African Law Commission’s 1998 proposals on class and public-interest actions, as well as the substantial case law dealing with sec. 38(a) own-interest actions combined with a strong element of public interest, to formulate proposals on how ‘public interest’ as well as standing for public-interest litigants should be interpreted and determined.
Keywords: South Africa; Constitution; Omar Hassan Ahmed Al-Bashir; International Criminal Court; Class actions; Public interest actions; Litigation